2011
DOI: 10.1117/1.3544585
|View full text |Cite
|
Sign up to set email alerts
|

Lipid-cell interactions in human monocytes investigated by doubly-resonant coherent anti-Stokes Raman scattering microscopy

Abstract: Abstract. We demonstrate that doubly-resonant coherent anti-Stokes Raman scattering can provide enhanced and highly specific contrast for molecules containing unique Raman-active small molecular groups. This combination provides contrast for molecules that can otherwise be difficult to discriminate by Raman spectroscopy. Here, human monocytes were incubated with either deuterated oleic acid or 17-octadecynoic acid (a fatty acid with an end terminal acetylene group). The carbon-deuterium stretching vibration of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 19 publications
0
21
0
Order By: Relevance
“…However, from the literature, monocytes were reported to uptake fatty acids from very low-density lipoprotein lipolysis products and formed small intracellular lipid droplets [44-46]. The lipid contents of monocytes were low overall and declined postprandially [45].…”
Section: Resultsmentioning
confidence: 99%
“…However, from the literature, monocytes were reported to uptake fatty acids from very low-density lipoprotein lipolysis products and formed small intracellular lipid droplets [44-46]. The lipid contents of monocytes were low overall and declined postprandially [45].…”
Section: Resultsmentioning
confidence: 99%
“…For example, van Manen et al used d 8 -arachidonic acid (AA) to label LDs in neutrophils, and observed close association between AA-enriched LDs and phagosome 41 . Xie et al 42 and Weeks et al 43 demonstrated that d 33 -oleic acid or d 2 -oleic acid could be used for CARS microscopic imaging of lipid droplet. With reduced non-resonant background in SRS, Zhang et al were able to reveal the cellular uptake of d 31 -palmitic acid and its incorporation into LDs and membrane 44 .…”
Section: Lipid Metabolismmentioning
confidence: 99%
“…CARS microscopy has been extensively applied to the study and visualization of LDs in cells and in tissue. [14][15][16][17][18] In particular, CARS microscopy enabled for the rst time the rapid label-free visualization of cellular and tissue lipid accumulations with chemical specicity and single cell and single lipid droplet sensitivity. In our own work, we have recently shown that we can quantify the effects of lipolysis products from very low density lipoproteins on cells and determine the average degree of unsaturation in individual cellular lipid droplets based on the analysis of single Raman peak ratios.…”
Section: Introductionmentioning
confidence: 99%